Adult convulsive status epileptic us: clinical, etiological, and predictors of outcome study from rural population of North India. (3rd June 2019) - Verma, Archana; Kiran, K.; Vaishya, Ganga Prasad; Kumar, Alok
Abstract: Aim: To determine the clinical profile, etiologies and predictors of mortality in patients with convulsive status epilepticus (CSE) among rural population of North India in view of limited published data on epidemiology and etiology of status epilepticus (SE) from developing countries. Methods : One hundred sixty-two consecutive adult patients with CSE were evaluated from 2016 to 2018 for demographic profile, etiologies and predictors of poor outcome. Results : The mean age was 41.71 ± 19.72 years. Most of the CSE cases were acute symptomatic (48.8%) type with central nervous system (CNS) infections (24.1%) being the predominant precipitating factor. Antiepileptic drugs (AEDs) noncompliance accounted for 34.9% of the cases with pre-existing epilepsy. The median duration of CSE was 5.5 h (IQR-3-10 h). 82.1% cases responded to the first line drugs and their response was related with duration of CSE ( p  = .0045). Case fatality was 16.0% and the predictors of the mortality were; low Glasgow Coma Scale (GCS) (OR =9.64, 95% CI= 2.064–45.02; p  = .0001), lack of response to first line drugs (OR =0.019, 95% CI= 0.003–0.11; p  = .0001) and absence of past history of epilepsy (OR =0.525, 95%CI =0.104–2.66; p  = .004). Conclusions : CNS infection and AEDs noncompliance were identified to be the major cause of CSE which can be potentially preventable. Present study signifies that prompt and successful control of infections appears to be the most efficient preventive approach. Level of consciousness as a potential predictor of poor outcome can be quickly accessible to the treating clinician in optimizing treatment strategies.